Rancang Bangun Mesin Pengepres Biji Jarak Dengan Penggerak Motor Bensin - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Kartono, Suyadi, Bambang Tjahyono, Sunarto (Teknis, 2014)
Pressing machine is used for pressing castor seeds (Ricinus communis ) to be castor oil that used as an alternative fuel. Making pressing machine have been selected from several designs, just by a gasoline motor elected, the selection of materials and the determination some component based on laboratory test and theoretical calculations. Also discussed about the process of working, assembly, financing, outcomes of designing and maintenance, the results of designing and making for castor seed of 9.65 kg capacity which can be processed in one hour, and the dimensions of the machine with a length of 900 mm, width 800 mm, height 800 mm with 5.5 HP power driven by gasoline motor.Key words : Pressing machine, castor seed, and gasoline motor.